Enriching urban spaces with ambient computing, the internet of things, and smart city design - Konomi, Shinʼichi; Roussos, George (Advances in human and social aspects of technology book series, 2017)
This book is a reference source for the latest scholarly material on the interaction between people and computing systems in contemporary society, showcasing how ubiquitous computing influences and shapes urban environments, highlighting the impacts of these emerging technologies from an interdisciplinary perspective